Enhancing digital literacy of potato farmers in the utilization of the Viazi Soko and agriBORA platforms for market linkages in Kenya - Barungi, Julian; Ssebwana, Achilley K; Okonya, Joshua; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Decision support tools, especially those that provide relevant data in a quick and user-friendly manner, are critical in helping farmers make better decisions in their day-to-day operations. This digital literacy training focused on utilization of the Viazi Soko and agriBORA digital platforms to facilitate access to farm output and input markets through aggregation, collective ordering, and contract farming targeting the potato processing industry. A field day was also organized for farmers to visit a potato demonstration farm in Mauche, Njoro subcounty, Nakuru County to learn about the good agronomic practices of potatoes including the benefits of using apical cuttings as a source of clean (disease-free) seed. Farmers were trained in good agronomic practices of seed and ware potato production, contract farming and use of digital platforms. The training enhanced capacities of 121 participants (55 males, 66 females) comprising farmers of potato, cereals and dairy, extension workers (agriprenuers, farmer service centers, producer cooperative members), Village based agents (digital connectors), and Nakuru and Nyandarua County Government Officials on the utilization of the Viazi Soko and agriBORA platforms for market linkages in Kenya. Viazi Soko and agriBORA tools are digital platforms aimed at improving decision making for farmers including weather advisory, linkage to input and output markets, agricultural credit and crop insurance services. The viazi soko platform provides an efficient way for sourcing and procuring quality farm inputs such as certified seeds, fertilizers, agrochemicals and services soil testing, mechanization, spray services, marketing information and extension. It is also used to help link farmers to market outlets and can be accessed via the Google Play Store, a web-based portal (www.npckviazisoko.com), and a USSD short code application (*483*331#). The agriBORA platform is an innovative suite of services that include agro-input lending, transactions check-out, and real-time crop monitoring. The platform can be accessed using USSD (*275#) codes for feature phones, Smart phone apps (AgriPOS, AgriKOPA, AgriHALA and agriMON) and over the Web (https://app.agribora.com). Plans were made with service providers (agriBORA and NPCK) to monitor the utilization of the two digital platforms to ensure that farmers remain active and get value for money.